GAYA BAHASA PERBANDINGAN DALAM KUMPULAN PUISI BIARKAN JARIKU KINI YANG MENGUNGKAPKANNYA KARYA KAWE ‘ARKAAN - Gita Kumala Dewi; Sumiharti Sumiharti (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2020)
The purpose of this research is to describe figurative language of comparison in the collection of poetry Biarkan Jariku Kini yang Mengungkapkannya by Kawe ‘Arkaan which consist of three aspects, they are: proverbs, personification, and depersonification. This research uses descriptive method with content analysis. The primary data of the research is the words which contain figurative language of comparison in the collection of the poetry Biarkan Jariku Kini yang Mengungkapkannya by  Kawe ‘Arkaan. Meanwhile the technique of collecting data is library study. Based on the result of the analysis, it can be found that there is figurative language in the collection of poetry Biarkan Jariku Kini yang Mengungkapkannya by Kawe ‘Arkaan. It has three aspects, they are provebs, personification, and depersonification. The result of the analysis shows: (1) 18 expressions of proverbs, (2) 51 expressions of personification, (3) no depersonification. The dominant of figurative language occured is personification.